Emerging and Innovative Theranostic Approaches for Mesoporous Silica Nanoparticles in Hepatocellular Carcinoma: Current Status and Advances - Tao, Yaoye; Wang, Jianguo; Xu, Xiao (Frontiers in Bioengineering and Biotechnology, 2020)
Hepatocellular carcinoma (HCC) is one of the most prevalent and lethal solid cancers globally. To improve diagnosis sensitivities and treatment efficacies, the development of new theranostic nanoplatforms for efficient HCC management is urgently needed. In the past decade, mesoporous silica nanoparticles (MSNs) with tailored structure, large surface area, highagents loading volume, abundant chemistry functionality, acceptable biocompatibility have received more and more attention in HCC theranostic. This review outlines the recent advances in MSNs-based systems for HCC therapy and diagnosis. The multifunctional nanocomposites that have both of therapy and diagnosis abilities are highlighted. And the precision delivery strategies of MSNs in HCC are also discussed. Final, we conclude with our personal perspectives on the future development and challenges of MSNs.